Kan grammatiske konstruktioner have semantisk prosodi? - Jensen, Kim Ebensgaard (Ny forskning i grammatik, 2017)
Drawing on a soft interpretation of the construction-grammatical notion of the lexicon-syntax continuum, this paper explores whether grammatical constructions can be said to display patterns of semantic prosody and discusses ways in which constructional semantic prosody as a theoretical construct would need to be defined such that two types of constructional semantic prosody are posed: inner semantic prosody, which applies to collocational fields in schematic positions in a construction, and outer semantic prosody, which applies to collocational fields in the construction’s co-text. Two admittedly sketchy and exploratory empirical investigations suggest that inner semantic prosody might be a viable theoretical concept, while outer semantic prosody does not seem to be viable.